An African ecofeminist exploration of the gendered and environmental facets of the Herero and Nama genocide as depicted in selected Namibian narratives of the genocide - Andima, Eva-Liisa (Stellenbosch : Stellenbosch University, 2025)
Thesis (DPhil)--Stellenbosch University, 2025.